Waking the ruin: Graham Harman’s object-oriented ontology, photogrammetry and the dami of Imbros - Sevcan Ercan; Joe Graham (Cogent Arts & Humanities)
Graham Harman’s object-oriented ontology (OOO) finds increasing interest across the arts and humanities, and offers a number of novel ways to rethink our relationship to architecture. Within the context of a philosophy that prioritises objects and stresses the looseness of the bond between objects and their own qualities, Harman’s recently articulated focus on ‘zeroing’ form and function in order to engage the withdrawn reality of buildings on an aesthetic level offers a case in point. Applying Harman’s metaphysics in conjunction with 3D photogrammetry treated as an aesthetic technique, this article interrogates a type of ruin – dami (plural damia) found on the North Aegean Island of Imbros/Gökçeada – with a view to stimulating them ‘awake’. Courtesy of a metaphor created to act as a guide, plus the production of a new sensual object – a digital 3D photogrammetric model acting as a proxy for the scanned entity sat atop a hillside – the article provides a detailed framework for allowing an engaged beholder to reimagine the damia in new and unexpected ways, contributing to the literature concerning how Harman’s OOO may be practically applied.